ANALISIS FRAMING MODEL PAN DAN KOSICKI DALAM BERITA PELECEHAN SEKSUAL ANAK PANTI ASUHAN PADA MEDIA ONLINE CNN INDONESIA DAN KUMPARAN.COM - Hikmatunisa, Azizah; Setiawan, Hendra (Universitas Tanjungpura, 2022)
This study aims to determine how the media frames the news it writes. The method used in this study is a qualitative descriptive method. The subjects in this study were two online news media, namely CNN Indonesia and Kumparan.com, with the object of research in the form of one news text from each media;